Assessing the State and Livelihood Opportunities Towards Sustainable and Ecosystem-Based Approaches: Insight from Keter Beel Area of Southern Bangladesh - Swarnoka, S.C.; Ahamed, M.J.; Masud, A.A.; Rahman, M.M. (Department of Geography, University of Colombo, 2024)
Keter Beel is a natural wetland that contributes to the local economy and food availability, specifically, as a centre point of biodiversity protection, ecosystem firmness, fisheries, and watershed management. Conversely, the present state and livelihood opportunities of this wetland are unrevealed. Therefore, this study emphasizes the water quality, ecosystem services, socio-economic and ecotourism well-being to assess the state and livelihood opportunities. The study showed that the water quality of this wetland is still in good condition. Notably, the local people provide their labor in this Beel in different activities of pisciculture for monthly payment. Thus, this wetland supports the villagers living in surrounding areas by contributing to their monthly income and it also has become a good source of fish consumption and grass collection for their cattle. At present, this wetland attracts a significant number of tourists nationally and has created substantial ecotourism potential. People select this spot as a beautiful nature-based refreshing destination. Every tourist spends a positive amount of cash on transportation to visit here, and their cost contributes to the local economy. However, despite these blessings, this tourism is informal in type, and there is no proper system to deal with tourists who create a disturbance in this environment. Hence, this study proposed a sustainable livelihood and management strategy framework integrating ecosystem values and functions with conservation and development processes for the welfare and benefits of wetland ecosystems.
Keywords: Livelihood; Sustainability; Ecosystem; Keter Beel; Bangladesh